Penyuluhan Dan Pendampingan Kader Dalam Screening Kanker Payudara di Desa Dasan Lekong: Counseling and Assistance for Cadres in Breast Cancer Screening in Dasan Lekong Village - Saskiyanti Ari Andini; Rita Sopiatun; Rusmini Rusmini (Indonesia Berdaya, 2026)
Breast cancer is one of the leading causes of death among women in Indonesia, mainly due to delayed early detection. Preventive efforts can be strengthened by empowering village health cadres to perform simple screening methods such as Breast Self-Examination (BSE) and Clinical Breast Examination (CBE). The counseling and mentoring program for cadres in Dasan Lekong Village aimed to improve their knowledge, skills, and confidence in recognizing early signs of breast cancer. Methods included lectures, interactive discussions, examination simulations, and field mentoring. The results showed increased cadre understanding of breast cancer screening techniques (SADARI). Moreover, cadres were able to apply these skills in assisting the community. In conclusion, cadre counseling and mentoring play an important role in strengthening early detection of breast cancer at the village level and supporting community health promotion and prevention efforts. Abstrak. Kanker payudara merupakan salah satu penyebab utama kematian pada perempuan di Indonesia, terutama akibat keterlambatan deteksi dini. Upaya pencegahan dapat dilakukan melalui peningkatan kapasitas kader kesehatan desa dalam melakukan skrining sederhana, seperti Pemeriksaan Payudara Sendiri (SADARI) dan Pemeriksaan Payudara Klinis (SADANIS). Kegiatan penyuluhan dan pendampingan kader di Desa Dasan Lekong bertujuan meningkatkan pengetahuan, keterampilan, serta kepercayaan diri kader dalam mengenali tanda awal kanker payudara. Metode yang digunakan meliputi ceramah, demonstrasi, dan simulasi pemeriksaan, serta pendampingan lapangan. Hasil kegiatan menunjukkan adanya peningkatan pemahaman kader mengenai teknik skrining kanker payudara sendiri (SADARI). Selain itu, kader mampu mengaplikasikan keterampilan tersebut dalam mendampingi masyarakat. Kesimpulannya, penyuluhan dan pendampingan kader berperan penting dalam memperkuat deteksi dini kanker payudara di tingkat desa, serta mendukung upaya promotif dan preventif kesehatan masyarakat.